Controlled Reperfusion Strategies Improve Cardiac Hemodynamic Recovery after Warm Global Ischemia in an Isolated, Working Rat Heart Model of Donation after Circulatory Death (DCD) - Farine, Emilie; Niederberger, Petra; Wyss, Rahel K.; Méndez-Carmona, Natalia; Gahl, Brigitta; Fiedler, Georg M.; Carrel, Thierry P.; Tevaearai Stahel, Hendrik T.; Longnus, Sarah L. (Frontiers in Physiology, 2016)
Aims: Donation after circulatory death (DCD) could improve cardiac graft availability, which is currently insufficient to meet transplant demand. However, DCD organs undergo an inevitable period of warm ischemia and most cardioprotective approaches can only be applied at reperfusion (procurement) for ethical reasons. We investigated whether modifying physical conditions at reperfusion, using four different strategies, effectively improves hemodynamic recovery after warm ischemia. Methods and Results: Isolated hearts of male Wistar rats were perfused in working-mode for 20 min, subjected to 27 min global ischemia (37°C), and 60 min reperfusion (n=43). Mild hypothermia (30°C, 10 min), mechanical postconditioning (MPC; 2x 30 sec reperfusion/ 30 sec ischemia), hypoxia (no O2, 2 min) or low pH (pH 6.8-7.4, 3 min) was applied at reperfusion and compared with controls (i.e. no strategy). After 60 min reperfusion, recovery of left ventricular work (developed pressure*heart rate; expressed as percent of pre-ischemic value) was significantly greater for mild hypothermia (62±7%), MPC (65±8%) and hypoxia (61±11%; p<0.05 for all), but not for low pH (45±13%), versus controls (44±7%). Increased hemodynamic recovery was associated with greater oxygen consumption (mild hypothermia, MPC) and coronary perfusion (mild hypothermia, MPC, hypoxia), and with reduced markers of necrosis (mild hypothermia, MPC, hypoxia) and mitochondrial damage (mild hypothermia, hypoxia). Conclusions: Brief modifications in physical conditions at reperfusion, such as hypothermia, mechanical postconditioning and hypoxia, improve post-ischemic hemodynamic function in our model of DCD. Cardioprotective reperfusion strategies applied at graft procurement could improve DCD graft recovery and limit further injury; however, optimal clinical approaches remain to be characterized.